Overpayment of tax: when does a taxpayer have a right to repayment - Silke, Jonathan M (Department of Commercial Law, 2021)
A recent decision of the House of Lords in England, Woolwich Building Society v Inland Revenue Commissioners (No 2) (1), is of great importance for taxpayers and has impact in the fields of constitutional, public and tax law. Although a decision of the courts of England, it has great significance for our law as well, especially in the light of two important recent decisions of our Appellate Division, CIR v First National Industrial Bank Ltd (2) and Willis Faber Enthoven (Pty)Ltd v Receiver of Revenue and Another (3). In the Woolwich Building Society case the Revenue had issued a demand under the Income Tax (Building Societies) Regulations 1986 to the plaintiff building society for payment of composite rate tax amounting to £56 998 221 on interest and dividends paid to investors between 30 September 1985 and 1 March 1986 and it had paid the tax claimed under protest. Plaintiff disputed the validity of the 1986 regulations but paid the amount assessed in three instalments commencing on 16 June 1986.The next day it applied for judicial review of the regulations to challenge the lawfulness of certain provisions and also issued a writ on 15 July to recover the amount paid as money had and received, together with interest thereon. In October 1990 the House of Lords confirmed that the sections of the regulations complained of were indeed ultra vires the enabling legislation(4).Plaintiff then continued its action for repayment and sought payment of interest on the capital from the dates of payment of the three instalments until judgment was given at first instance in the High Court on 31 July 1987. Inland Revenue accepted only a moral obligation to repay the principal amount of £57 million, together with interest from the date of first judgment in Plaintiff's favour. However, the Revenue claimed that any such repayment would be a matter of administrative grace only and not of legal entitlement, with the result that no interest was due for the period between the original payment and the date of that High Court judgment. Plaintiff would only have been entitled to recover the interest in issue if it would be able to show that it had been entitled in law to repayment of the principal sums as from the dates of their first payment. The main issue before the House of Lords was whether, and in what circumstances, a taxpayer is entitled, as a matter of right, to recover sums paid to the Revenue pursuant to unlawful